Characterization of Anti-Müllerian Hormone (AMH) Gene in Buffaloes and Goats - Gautam, Devika; Vats, Ashutosh; Pal, Prasanna; Haldar, Avijit; De, Sachinandan (Frontiers in Veterinary Science, 2021)
The Anti-Mullerian Hormone (AMH) is a member of the transforming growth factor beta (TGF-β) superfamily, playing a significant role in cell proliferation, differentiation and apoptosis. In females, AMH is secreted throughout their reproductive life span from ovaries, whereas in males it is secreted by gonadal cells at a very early stage of testicular development. AMH is a promising marker of ovarian reserve in women and can be used to measure the female reproductive lifespan. In the present study, we cloned and sequenced the GC rich AMH gene from Indian riverine buffalo (Bubalus bubalis) and goat (Capra hircus). Obtained sequences were compared to the AMH sequences of other mammals, and corresponding amino acid sequences revealed that the caprine and bovine AMH sequences are more closely related to each other than to those of other mammals. Furthermore, we analyzed the chromosomal localization of AMH genes in mammalian species to understand potential syntenic relationship. The AMH gene is localized between the sequences for the SF3A and JSRP1 genes and maintains this precise location in relation to other nearby genes. The dN/dS ratio of AMH gene did not indicate any pressure for either positive or negative selection; thus, the physiological function of the AMH gene in the reproduction of these two ruminant species remains very vital. Similar to other mammals, the AMH gene may be an important indicator for regulating female reproductive biology function in bovine, cetacean, caprine and camelidae.